2016
DOI: 10.1016/j.jds.2016.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Association between burnout and depressive symptoms among Turkish dentists

Abstract: Background/purpose Health care professionals including dentists can experience increased professional burnout. The aim of the study was to evaluate the association between depressive symptoms and burnout among Turkish dentists. Materials and methods This study was conducted among a Turkish dentist sample in Ankara (Turkey) between February 2015 and August 2015. From a total of 500 dentists, 337 were included. A self-structured questionnaire, Maslach Burnout Inventory (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
38
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 27 publications
4
38
1
7
Order By: Relevance
“…Previous studies have demonstrated that the risk of burnout increases in occupations which expose individuals to an emotional burden and stress, as faced by physicians, requiring busy working hours, heavy workload, providing care to deadly ill patients, and providing support as necessary to the patients and their closed ones (17)(18)(19). Aktug et al (20) reported that burnout was particularly common at the sub-dimensions of emotional exhaustion and desensitization among resident physicians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that the risk of burnout increases in occupations which expose individuals to an emotional burden and stress, as faced by physicians, requiring busy working hours, heavy workload, providing care to deadly ill patients, and providing support as necessary to the patients and their closed ones (17)(18)(19). Aktug et al (20) reported that burnout was particularly common at the sub-dimensions of emotional exhaustion and desensitization among resident physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies in the literature reported that burnout scores were higher among female compared to male physicians, some others did not demonstrate any significant effect of gender (18,20,21,26,27). Additionally, some studies reported that internet use was more common among men and their addiction scores were higher, while there are also studies reporting no significant difference (28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…We found a signi cant relationship between burnout and depressive symptoms . It is still debatable whether burnout syndrome and depressive symptoms arise from the same situation, or are two different conditions (26). There was a statistically signi cant positive correlation between all three burnout subscales (EE, DP, and PA) and depressive symptoms .…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Huri ve ark.nın diş hekimleri üzerinde yürüttüğü bir çalışmada, ortalama BDI 13,32±8,51 olarak saptanmış ve bu değerin kadın hekimlerde anlamlı dü-zeyde yüksek olduğu bulunmuştur. 26 Bu çalışmaya katılan öğrencilerin ortalama BDI skoru 19,03±13,66 olarak saptanmış olup; kızlarda 18,38±12,98, erkeklerde ise 19,58±14,23'tür. Alfaris ve ark.…”
Section: Discussionunclassified